Prevalence and characteristics of metabolic dysfunction-associated steatohepatitis among pediatric patients in the MarketScan Databases - Kennedy M. Peter-Marske; Xiao Zhang; Tongtong Wang; Xinyue Liu; Gail Fernandes; Samuel S. Engel; Ravi Shankar (PLoS ONE, 2025)
Introduction There are few epidemiologic studies of the prevalence of metabolic dysfunction-associated steatohepatitis (MASH) among pediatric populations. Objective To estimate the cross-sectional prevalence of MASH in the pediatric (<18 years) populations of Merative TM MarketScan® Commercial Database (Commercial) and Merative TM MarketScan® Multi-State Medicaid Database (Medicaid). Methods Pediatric patients with ≥1 medical encounter from 1/1/2020 to 12/31/2020 and ≥6 months of continuous enrollment before the most recent medical encounter were included. MASH was confirmed by an ICD-10-CM diagnosis code for MASH (K75.81) in the medical history since 1/1/2016. Results A total of 1,476 and 410 pediatric MASH patients were identified in Medicaid and Commercial databases respectively, with a prevalence of 0.036% (95% confidence interval (CI): 0.034%, 0.038%) in Medicaid, as compared to 0.011% (95% CI: 0.010%, 0.012%) in Commercial. Prevalence of MASH increased by age. MASH was more prevalent in those who were male, obese, had T2D, and had metabolic syndrome. Among all pediatric MASH patients, the majority were ≥10 years old, male, and obese. Discussion MASH is more prevalent among pediatric patients with comorbid conditions such as metabolic syndrome, obesity, and T2D, which appears to be similar to young adults. Rising prevalence of childhood obesity and related comorbid conditions, and the progressive nature of MASH, make this an area of increasing medical need. Prescreening MASH among high-risk patients with these comorbidities is needed for target intervention.